Trabalho com mulheres: contribuindo com processos de emancipação de mulheres das classes populares - Carmo, Onilda Alves do [UNESP]; Fontenla, Carolina Paulino [UNESP]; Martins, Núbia Sanches [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
From the observed demands about the challenges faced by women inhabit in the peripheal areas and rural zone of the municipality of Franca, the Margarida Alves group develops workshops with the aim of empowering them so that themselves can be constituted as subject of rights. Many of these women, in most everyday situations, are inserted in a context of violence be it physical, psychological or moral through the prosecution of various obligations attributed to them and for inequalities they suffered in different spaces. In view of this, they should have the chance to compose as subject in the way that they become aware of their being and become free beings. The methodology of the workshops has the Popular Education orientation for taking the reality and the experiences as much of the life as the work perspective the women of popular class participants of Social Assistance policies. Ultimately, the project seeks a contribution so that these women be able to establish more equitable relations in the daily life in the family. Therefore, the aim is to cooperate in order to implement in the municipality of Franca gender policies of greater effectiveness for women, specifically for those coming from the popular classes.

A partir das demandas observadas acerca dos desafios enfrentados pelas mulheres que habitam as áreas periféricas e a zona rural do município de Franca, o grupo Margarida Alves desenvolve oficinas com a finalidade de empoderá-las para que elas mesmas possam se constituir enquanto sujeitas de direitos. Muitas dessas mulheres, na maioria das situações cotidianas, estão inseridas em um contexto de violência seja esta moral, psicológica ou física por meio da inculpação das diversas obrigações a elas atribuídas e das desigualdades por elas sofridas em diferentes espaços. Em vista disso, devem ter a chance de se comporem enquanto sujeitas de forma que tomem consciência de seu ser e transformem-se em seres livres. A metodologia das oficinas tem por orientação a Educação Popular por tomar como perspectiva a realidade e a experiência tanto de vida quanto de trabalho de mulheres da classe popular participantes de Políticas de Assistência Social. Em última instância, o projeto busca uma contribuição a fim de que essas mulheres consigam estabelecer relações de maior equidade no cotidiano em família. Portanto, visa- se cooperar para que se implemente no município de Franca políticas públicas de gênero de maior efetividade para as mulheres, especificamente para aquelas provenientes das classes populares.
Keywords: Gender relations; Popular class; Social rights; Relações de gênero; Classe populares; Direitos sociais